Transforming learning environments strategies to shape the next generation - Miller, Fayneese S. (Bingley, U.K. : Emerald, 2012)
With the influence and pressures of the globalized economy, education systems are at a crossroads and need to find a place and/or identity that reflect new or transformed realities for learning environments. Questions such as to what extent, in what way, and how are we doing will need to be raised and answered before learning environments can begin the work necessary to create people who are ready to enter the globalized workforce. This book will present chapters written from a variety of perspectives to address the question "what is needed within systems of education to prepare the next generation of leaders for a competitive global environment?" The authors focus on such topics as online learning, technology, leadership, and English Language Learners to show the challenges to traditional educational practices and the ways in which learning environments are responding to the new reality of globalization.
Introduction / Fayneese S. Miller -- Developing teacher leaders to transform classrooms, schools, and communities / Maureen D. Neumann, Laura C. Jones, P. Taylor Webb -- Leading for change : designing a model of transformational leadership through the Carnegie project on the education doctorate / Olga M. Welch -- Teaching about religious and spiritual difference in a global society / Robert J. Nash, Vanessa S. Eugenio -- Incorporating concepts of global citizenry into student-centered academic advising / DeMethra LaSha Bradley -- Collaborative partnerships for capacity building through professional development / Mary Barbara Trube, Bonnie L. Prince, Renée A. Middleton -- Learning starts with design : using universal design for learning (UDL) in higher education course redesign / Holly Buckland Parker -- The value of value-added methods / Valerie Sullivan -- Responsive technologies for young adolescents / John M. Downes, Penny A. Bishop -- 'This I believe' : addressing cultural competency with the digital narratives of middle grades English language learners / Cynthia Reyes -- From Pong to PS3 : how video games enhance our capacity to learn and build community / Laurie M. Gelles -- Game changers for transforming learning environments / David Gibson.
Print version record
Keywords: Education -- Research; Education -- Comparative; Education -- Aims & Objectives; Literacy strategies; Philosophy & theory of education; Leadership -- Study and teaching; Learning; Education and globalization